Rifampin-Releasing Triple-Layer Cross-Linked Fresh Water Fish Collagen Sponges as Wound Dressings - Hartinger, Jan; Lukáč, Peter; Mlček, Mikuláš; Popková, Michaela; Suchý, Tomáš; Šupová, Monika; Chlup, Hynek; Horný, Lukáš; Závora, Jan; Adámková, Václava; Slanař, Ondřej; Kozlík, Petr; et al. (BioMed research international, 2020)
Objectives: Surgical wounds resulting from biofilm-producing microorganisms represent a major healthcare problem that requires new and innovative treatment methods. Rifampin is one of a small number of antibiotics that is able to penetrate such biofilms, and its local administration has the potential to serve as an ideal surgical site infection protection and/or treatment agent. This paper presents two types (homogeneous and sandwich structured) of rifampin-releasing carbodiimide-cross-linked fresh water fish collagen wound dressings. Methods: The dressings were prepared by means of the double-lyophilization method and sterilized via gamma irradiation so as to allow for testing in a form that is able to serve for direct clinical use. The mechanical properties were studied via the uniaxial tensile testing method. The in vivo rifampin-release properties were tested by means of a series of incubations in phosphate-buffered saline. The microbiological activity was tested against methicillin-resistant staphylococcus aureus (MRSA) employing disc diffusion tests, and the in vivo pharmacokinetics was tested using a rat model. A histological examination was conducted for the study of the biocompatibility of the dressings. Results: The sandwich-structured dressing demonstrated better mechanical properties due to its exhibiting ability to bear a higher load than the homogeneous sponges, a property that was further improved via the addition of rifampin. The sponges retarded the release of rifampin in vitro, which translated into at least 22 hours of rifampin release in the rat model. This was significantly longer than was achieved via the administration of a subcutaneous rifampin solution. Microbiological activity was proven by the results of the disc diffusion tests. Both sponges exhibited excellent biocompatibility as the cells penetrated into the scaffold, and virtually no signs of local irritation were observed. Conclusions: We present a novel rifampin-releasing sandwich-structured fresh water fish collagen wound dressing that has the potential to serve as an ideal surgical site infection protection and/or treatment agent.
Keywords: Rifampin; Animals; Rats, Wistar; Bandages; Wound Healing; Collagen; rifampin; kolagen; Fishes; Anti-Bacterial Agents; methicilin rezistentní Staphylococcus aureus; infekce chirurgické rány; ryby; Fresh Water; Surgical Wound Infection; Male; sladká voda; hojení ran; krysa rodu Rattus; biofilmy; zvířata; mužské pohlaví; antibakteriální látky; Biofilms; Rats; obvazy; Methicillin-Resistant Staphylococcus aureus; potkani Wistar